Functional analysis of a novel SCN5A mutation G1712C identified in Brugada syndrome - Chen, Yan-Yu; Liu, Shen-Rong; Xie, Liang-Zhen; Zhu, Ting-Yan; Chen, Yi-Zhen; Deng, Xiao-Jiang; Meng, Su-Rong; Peng, Jian (Nan fang yi ke da xue xue bao = Journal of Southern Medical University, 2016)
To elucidate the molecular and electrophysiological mechanisms of Brugada syndrome through functional analysis of a novel SCN5A gene mutation G1712C. A recombinant plasmid pRc<CMV-hH1 containing the mutant human cardiac sodium channel α subunit (hH1) cDNA was constructed using in vitro PCR-based site-directed mutagenesis technique. LipofectamineTM 3000 was used to transfect the plasmid DNA into HEK293 cell line to induce stable expression of Na channel β1-subunit, and the positive colonies were selected by screening with G418.The standard liposome method was used to transiently transfect HEK293 cells with either the wild-type or mutant Na channel subunits (hH1 and mhH1, respectively), and the macroscopic Na currents were recorded using whole-cell patch-clamp technique. Data acquisition and analysis, generation of voltage commands and curve fitting were accomplished with EPC-10, PatchMaster and IGOR Pro 6.0. An HEK293 cell line that stably expressed Na channel β1-subunit was successfully established. After tra